Achieving health security in Nigeria: A strategic blueprint for addressing psychoactive substance use (2019)
Introduction: Psychoactive substance use is an important component of health and national security. Nigeria has evolved from a largely transit nation for psychoactive substances to a high consumption nation. Increasing rates of use result in a concurrent rise in crime rates and insecurity, as well as road traffic accidents. The use of psychoactive substances is also implicated in episodes of civil strife, conflicts and wars, such as the ongoing Boko Haram insurgency in North East Nigeria. This observation is likely to worsen over time if there is no coherent and strategic plan to halt and reverse this trend. The forecast portends higher crime rates, heightened insecurity, civil unrest and violent conflicts by 2050, if the rising trend of psychoactive substance use is not reversed. It is a scenario that will not augur well for the stability of Nigeria and the West African region. Methods: A narrative review of the published literature, as well as expert opinion deliberations was utilized to develop a comprehensive analysis of the strategic strengths, weaknesses, opportunities and threats (SWOT) of psychoactive substance use and health security implications for Nigeria. Results: An array of the unique strengths and opportunities are spelt out; along with the inherent weaknesses and threats that should be taken into consideration in mapping out strategies to address the clear and present danger from the rising use of psychoactive substances in Nigeria. Conclusion: Recommended interventions should focus on public awareness campaigns, utilizing behaviour change communication strategies – with a special focus on prevention, mental health promotion activities, training and re-training of regulatory agencies, development and revision of existing policies, as well as better policing and enforcement of access restriction.